Analisis Tingkat Kepuasan Pelanggan Terhadap Kualitas Pelayanan Berdasarkan Indeks Kepuasan Pelanggan Pada CV.Lombok Lalu Travel - Baiq Vivin Maelanti; Baiq Ertin Helmida; Faizatul Fajariah (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This research aims to determine and analze the extent of Customer Satisfaction Level towards the Service Quality at CV. Lombok Lalu Travel. The population in this study consisted of 272 customers, using a simple radom sampling technique, resulting in a simple size of 54 customers. The Customer Satisfaction Index (CSI) was calculated in this study to assess the degree of alignment between customers expectations and perceived performance. It measures the difference between customers perceived performance and their expectations. The research method used in this study is descriptive research, with data collection using questionnaires distributed through google form. The data was then processed using SPPS 25 to assess the validity and reliability of each attribute. The results based on the Customer Satisfaction Index at CV. Lombok Lalu Travel obtained a score of 89%, indicating that the customers of are “very satisfied” with the service quality performance. Based on the calculations using the Customer Satisfaction index “responsible for providing services” and “ready to serve customers when traveling” received the lowest scores, suggesting in its service is more prepared in managing customer schedules according to the specified time.